Analysis of the Diagnosis’s Inaccuracy Codes for Infection Cases in Dahlia Ward’s Inpatients at Majenang Regional Hospital - Azizah, Syifa Khurotun; Hakim, Agya Osadawedya; Gunawan , Gunawan (Universitas Muhammadiyah Sidoarjo, 2024)
The large number of infection cases in Indonesia has caused the number of BPJS claims related to these cases to continue to increase. The claim process carried out by the hospital must go through various stages in order to be claimed, including the coding process. The medical recorder's role as a coder is responsible for the correctness and accuracy of the code for a diagnosis that has been determined by medical personnel (doctors). Inaccuracies in diagnosis codes will impact the effectiveness of health service data and information management as well as pending claims. Pending claims that occur due to inaccuracies can impact hospital cost profit which will result in the hospital experiencing losses. Based on a preliminary study conducted in the Dahlia Ward, Majenang Regional Hospital, 3 medical records with incorrect codes were found (3.54%) out of 58 medical records. This study aims to calculate the inaccuracy of diagnosis codes for cases of infection for inpatients in the Dahlia Ward, Majenang Regional Hospital and identify the factors that cause inaccurate diagnosis codes for cases of infection for inpatients in the Dahlia Ward, Majenang Hospital.The research method used is a qualitative method with a narrative descriptive design. Data collection techniques were carried out using two methods, namely observation and interviews. Interviews were conducted to obtain reasons for inaccurate diagnosis codes, while observations were used to verify interview results. There were 3 resource persons in this study, namely the head of medical records and 2 inpatient coders. The research results showed that inaccuracies occurred due to incomplete diagnosis writing by the DPJP, such as doctors tending to write abbreviations, and coders tending to use rote memorization in determining diagnosis codes.